Employee Assistance Programs: Balancing Increased Productivity and Engagement Among Employees with Equal Employment and Legal Complience - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition Forum, 2019)
Managing the impact of employees' personal and work-related difficulties on workplace productivity is becoming increasingly salient for organizations. Employee Assistance Programs (EAPs) are one approach to help improve the quality of life for employees and maximize their productivity. While EAPs have many benefits, potential negative ramifications and legal considerations must also be considered. This article highlights some important cases and the best practices for organizations to utilize in creating clear organizational policies that align with equal employment opportunity and privacy laws in collaboration with legal and human resources professionals and employee assistance providers to reduce or eliminate potential liability.
Keywords: Absenteeism; Affirmative action; Business And Economics; Complaints; Confidentiality; Costs; Employees; Employers; Employment discrimination; Human resource management; Labor law; Performance evaluation; Productivity; Sexual harassment; dept.mgt; peer-reviewed; ⛔ No DOI found